Why Still Home Deliveries in Urban Slum Dwellers? - S D Kotnis; R M Gokhale; M V Rayate (Medsci Publications, 2012)
Background: The current policy of Government of India under N.R.H.M.and R.C.H. is to encourage an institutional delivery which is an important step in lowering the maternal mortality. Methodology: Cross- sectional, community based descriptive study. Conducted in Urban Health Centre area in September 2007, to study various factors associated with home deliveries. Present study reports the home delivery cases in the last six years in the slum areas under Urban Health Centre. A pretested & prestructured semi-open-ended proforma was used. Results: Out of total 1441 deliveries 91(6.32%) were home deliveries, 62(68.13%) mothers were literate. 71 (78.02%) belonged to S.E. class III & lV.73 (80.22%) from joint families. 72(79.12%) deliveries were in multiparous women. 61, (67.03%) were conducted by untrained persons. Common reasons were- custom (26.37%), spontaneous delivery (24.18%), monetary problems(25.27%), homely atmosphere (13.19%), health services not satisfactory (10.99%). Conclusion: The leading factors associated as evident are low socio economic status, customs, spontaneous delivery , monetary problems, and homely atmosphere. Health education to mothers and dialogue with the health staff can be the remedial measures to encourage hospital deliveries.